Endocytic pathways regulate Toll-like receptor 4 signaling and link innate and adaptive immunity - Husebye, Harald (2006)
Immune responses are initiated when molecules of microbial origin are sensed by the Toll-like receptors (TLRs). We now report the identification of essential molecular components for the trafficking of the lipopolysaccharide (LPS) receptor complex. LPS was endocytosed by a receptor-mediated mechanism dependent on dynamin and clathrin and colocalized with TLR4 on early/sorting endosomes. TLR4 was ubiquitinated and associated with the ubiquitin-binding endosomal sorting protein hepatocyte growth factor-regulated tyrosine kinase substrate, Hrs. Inhibition of endocytosis and endosomal sorting increased LPS signaling. Finally, the LPS receptor complex was sorted to late endosomes/lysosomes for degradation and loading of associated antigens onto HLA class II molecules for presentation to CD4(+) T cells. Our results show that endosomal trafficking of the LPS receptor complex is essential for signal termination and LPS-associated antigen presentation, thus controlling both innate and adaptive immunity through TLR4.